Labor Unions and American Poverty - Tom VanHeuvelen; David Brady (ILR Review, 2022)
American poverty research largely neglects labor unions. The authors use individual-level panel data, incorporate both household union membership and state-level union density, and analyze both working poverty and working-aged poverty (among households led by 18- to 64-year-olds). They estimate three-way fixed effects (person, year, and state) and fixed-effects individual slopes models on the Panel Study of Income Dynamics (PSID), 1976–2015. They exploit the higher quality income data in the Cross-National Equivalent File—an extension of the PSID—to measure relative (<50% of median in current year) and anchored (<50% of median in 1976) poverty. Both union membership and state union density have statistically and substantively significant negative relationships with relative and anchored working and working-aged poverty. Household union membership and state union density significantly negatively interact, augmenting the poverty-reducing effects of each. Higher state union density spills over to reduce poverty among non-union households, and there is no evidence that higher state union density worsens poverty for non-union households or undermines employment.
doi:10.3886/E137301V1
Keywords: 330; unionization; poverty; labor union; longitudinal; working poverty